PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI SMKN 1 GEDONG TATAAN - Nanda Pramana Putra; Aprianis Aprianis; Yudhinanto Cahyo Nugroho (Jurnal Manajemen dan Bisnis (JMB), 2021)
ABSTRACTThe purpose and benefits of this study are to determine the effect of the work environment on the performance of 1 Gedong Tataan Vocational School employees and are expected to increase their knowledge and experience and broaden their insights in applying theories and contributions of useful thinking about the influence of the work environment on the performance of employees inVocational High School 1 Gedong Tataan . The research method used is based on quantitative data analysis techniques. The results showed a regression equation Y = 23,991 + 0,395 X, the equation showed that if there was an increase in work environment variables of 1 unit then the performance would increase by 0.395, while the magnitude of the effect of the work environment was known through the calculation of the coefficient of determination (r²) = 27.7% This means that employee performance is influenced by 27.7% by the work environment while the remaining 72.3% is determined by other factors. Keywords: physical work environment, non physical work environment, employee performance